Offensive tactical thinking and its relationship to intelligence for youth soccer players in Al-Muthanna Governorate clubs - محمد رحيم ركان ASAAD TAREQ AHMED (Mustansiriyah Journal of Sports Science, 2024)
The tactical preparation is the container in which all types of preparation (physical, skillful, psychological, and cognitive (mental) are mixed. The integration, mixing and interdependence of the types of these preparations helps positively in preparing a good plan. All of this contributes to achieving the goal of sports training, which is winning matches. Thus, the importance of The research deals with the tactical aspect of the study as one of the important aspects in the numbers of soccer players, and an important element of level determination because of its great importance in deciding the outcome of the match. Developing them, and this requires them to train and exercise continuously so that the players can know all their tactical capabilities and fully realize what each colleague will do, and know how to take advantage of the individual advantages of each of them in all playing situations. The aim of the research is to identify the relationship between tactical and offensive thinking and intelligence for club players Al-Muthanna Governorate with youth football, and the researchers hypothesized that there is a significant relationship between offensive tactical thinking and intelligence. The descriptive approach is based on the methods of survey, correlational, and normative studies, due to its suitability in achieving the objectives of the research. The research community included players of Al-Muthanna Governorate clubs for the football season (2021-2022), whose number is (137) players, distributed among the following sports clubs: (Samawah, Al-Muthanna, Al-Salman, Al-Khader The RAVEN test for successive matrices was applied to measure intelligence, and after conducting the requirements required to prepare the tactical thinking test in the offensive third of the football field in its final form, which consisted of (55) items, the offensive tactical thinking test was applied Raven’s intelligence test on the research sample. The researchers concluded that it was found to build a test of offensive tactical thinking for the players of Muthanna Governorate football clubs, as well as the existence of a positive significant relationship between the level of offensive tactical thinking with the intelligence variable of football players. The researchers recommended the use of the offensive tactical thinking test (offensive tactical positions) by football coaches. And the coaches emphasize the importance of the level of intelligence when choosing the players of the football team, along with developing the tactical thinking and knowledge of the football players during the training units. As well as benefiting from the test as a training program to develop thinking, tactical knowledge and offensive tactical behavior for football players.